Platelets stored in whole blood at 4°C: in vivo posttransfusion platelet recoveries and survivals and in vitro hemostatic function. Issue 6 (12th April 2019) - Slichter, Sherrill J.; Fitzpatrick, Lynda; Osborne, Barbara; Christoffel, Todd; Gettinger, Irena; Pellham, Esther; Bailey, S. Lawrence; Jones, Mary Kay; Herzig, Maryanne C.; Cap, Andrew P.
Abstract : BACKGROUND: Ordinarily, whole blood (WB) is separated into components before storage. We assessed the posttransfusion viability and function of platelets (PLTs) if they were stored within WB at 4°C. STUDY DESIGN AND METHODS: Whole blood was obtained from 30 normal subjects and stored at 4°C without agitation for 12 days and for 10, 15, or 22 days with agitation. After WB storage, a PLT concentrate was prepared, and a fresh PLT sample was obtained from each donor. The stored PLTs were labeled with 111 In and the fresh with 51 Cr, and both were simultaneously transfused into their donor. Blood samples were obtained after transfusion to determine PLT recoveries and survivals. PLT samples from WB before and after storage were also assayed for PLT function and biochemistry. RESULTS: After storage for 12 days without WB rotation, poststorage PLT counts averaged only 49 ± 12% of baseline values. After storage for 10, 15, or 22 days with end‐over‐end WB rotation, PLT counts averaged 76 ± 14% of baseline values. Fifteen‐day poststorage radiolabeled PLT recoveries averaged 27 ± 11% (49 ± 16% of fresh), and survivals averaged 1.2 ± 0.4 days (16 ± 6% of fresh). in vitro assays demonstrated marked PLT activation after any storage time, and although PLT function decreased over time, stored PLTs were still considered acceptable. CONCLUSION: These data suggest that, during rotated WB storage at 4°C for up to 15 days, PLT yields, poststorage PLT recoveries and survivals, and PLT function should be sufficient to support the short‐term hemostatic needs of traumatized patients.